Population-based BRCA1/2 testing programmes are highly acceptable in the Jewish community: results of the JeneScreen Study. Issue 3 (3rd June 2022) - Tiller, Jane M; Cousens, Nicole E; Kaur, Rajneesh; Rowley, Simone; Ko, Yi-An; Mahale, Sakshi; Bankier, Agnes; Meiser, Bettina; Barlow-Stewart, Kristine; Burnett, Leslie; Jacobs, Chris; James, Paul; et al.
Abstract : Background: Ashkenazi Jewish (AJ) people have a higher incidence of BRCA1/2 pathogenic variants (PVs) than unselected populations. Three BRCA -Jewish founder mutations (B-JFMs) comprise >90% of BRCA1/2 PVs in AJ people. Personal/family cancer history-based testing misses ≥50% of people with B-JFM. Methods: We compared two population-based B-JFM screening programmes in Australia—using (1) an online tool (Sydney) and (2) in-person group sessions (Melbourne). Results: Of 2167 Jewish people tested (Sydney n=594; Melbourne n=1573), 1.3% (n=28) have a B-JFM, only 2 of whom had a significant cancer family history (Manchester score ≥12). Pretest anxiety scores were normal (mean 9.9±3.5 (6–24)), with no significant post-result change (9.5±3.3). Decisional regret (mean 7.4±13.0 (0–100)), test-related distress (mean 0.8+/2.2 (0–30)) and positive experiences (reverse-scored) (mean 3.4±4.5 (1–20)) scores were low, with no significant differences between Sydney and Melbourne participants. Post-education knowledge was good overall (mean 11.8/15 (±2.9)) and significantly higher in Melbourne than Sydney. Post-result knowledge was the same (mean 11.7 (±2.4) vs 11.2 (±2.4)). Participants with a B-JFM had higher post-result anxiety and test-related distress and lower positive experiences, than those without a B-JFM, but scores were within the normal range. Family cancer history did not significantly affect knowledge or anxiety, or pretest perception of B-JFM or cancer risks. Most participants (93%) were satisfied/very satisfied with the programme. Conclusion: Both B-JFM screening programmes are highly acceptable to Australian Jewish communities. The programme enabled identification of several individuals who were previously unaware they have a B-JFM, many of whom would have been ineligible for current criteria-based testing in Australia.